Risk of major comorbidities among workers with hemophilia: A 14-year population-based study. Issue 6 (February 2018) - Chu, Wei-Min; Ho, Hsin-En; Wang, Jiaan-Der; Chan, Wei-Cheng; Liou, Yi-Sheng; Ho, Wen-Chao; Hu, Sung-Yuan; Tsan, Yu-Tse
Abstract : Abstract: Multiple comorbidities, especially musculoskeletal dysfunction and cerebrovascular disease, remain barriers to normal social participation among persons with hemophilia (PWH). However, the relative health effects of such comorbidities on workers with hemophilia have seldom been explored. In this study, we investigated the incidence of comorbidities and their risk factors among workers with hemophilia. The study compared the incidence and risk factors of the major comorbidities of 411 workers with hemophilia enrolled in Taiwan's National Health Insurance Research Database between 1997 and 2010 with an age- and sex-matched general population. Compared with the general population, workers with hemophilia had higher risks for hemorrhagic stroke, arthritis/arthropathy, and knee/hip replacement among workers with hemophilia after multivariate adjustment, with hazard ratios (95% CI) of 4.60 (2.81–7.53), 4.03 (3.34–4.87), and 1.29 (1.10–1.41), respectively. Disorder of joints, hemophilia-related arthritis/arthropathy, hemorrhagic stroke, and knee/hip replacement remain significant comorbidities among workers with hemophilia, which will result in increased social burden. Policymakers and employers should apply appropriate interventions to help prevent productivity losses, reduced workforce participation, sick leave, and work disability among hemophilia workers. Abstract : Supplemental Digital Content is available in the text